Cellulose nanofiber aerogel as a promising biomaterial for customized oral drug delivery - Bhandari J (Dove Medical Press, 2017)
Jyoti Bhandari,1 Harshita Mishra,1 Pawan Kumar Mishra,2 Rupert Wimmer,2,3 Farhan J Ahmad,1 Sushama Talegaonkar1 1Department of Pharmaceutics, Jamia Hamdard, New Delhi, India; 2Department of Wood Science, Mendel University in Brno, Brno, Czech Republic; 3Institute for Natural Materials Technology, Department of Agrobiotechnology, IFA-Tulln, University of Natural Resources and Life Sciences, Vienna, Austria Abstract: Cellulose nanofiber (CNF) aerogels with favorable floatability and mucoadhesive properties prepared by the freeze-drying method have been introduced as new possible carriers for oral controlled drug delivery system. Bendamustine hydrochloride is considered as the model drug. Drug loading was carried out by the physical adsorption method, and optimization of drug-loaded formulation was done using central composite design. A very lightweight-aerogel-with-matrix system was produced with drug loading of 18.98%±1.57%. The produced aerogel was characterized for morphology, tensile strength, swelling tendency in media with different pH values, floating behavior, mucoadhesive detachment force and drug release profiles under different pH conditions. The results showed that the type of matrix was porous and woven with excellent mechanical properties. The drug release was assessed by dialysis, which was fitted with suitable mathematical models. Approximately 69.205%±2.5% of the drug was released in 24 hours in medium of pH 1.2, whereas ~78%±2.28% of drug was released in medium of pH 7.4, with floating behavior for ~7.5 hours. The results of in vivo study showed a 3.25-fold increase in bioavailability. Thus, we concluded that CNF aerogels offer a great possibility for a gastroretentive drug delivery system with improved bioavailability. Keywords: cellulose nanofiber, aerogel, controlled release, gastroretentive, floating behavior, swelling behavior, mucoadhesion, bioavailability